Measurement of the electron charge asymmetry in inclusive W production in pp collisions at √s=7TeV - Chatrchyan, S. (2012)
A measurement of the electron charge asymmetry in inclusive pp→W+X→eν+X production at √s=7TeV is presented based on data recorded by the CMS detector at the LHC and corresponding to an integrated luminosity of 840pb -1. The electron charge asymmetry reflects the unequal production of W + and W - bosons in pp collisions. The electron charge asymmetry is measured in bins of the absolute value of electron pseudorapidity in the range of |η|<2.4. The asymmetry rises from about 0.1 to 0.2 as a function of the pseudorapidity and is measured with a relative precision better than 7%. This measurement provides new stringent constraints for parton distribution functions.